Influence of convection drying with hot air on the physicochemical and phytochemical properties of green banana flour (Musa cavendish) - Espinoza-Espinoza, Luis Alfredo; Juárez-Ojeda, Carlos Eduardo; Ruiz-Flores, Luis Alberto; Moreno-Quispe, Luz Arelis; Anaya-Palacios, Mirtha Susana; Cárdenas-Quintana, Haydée (Frontiers in Sustainable Food Systems, 2023)
The present study focuses on the effect of different drying temperatures (DT) (40, 60 and 80°C) and the combination of banana slice thicknesses (BST) (2 and 4 mm) on the physicochemical properties and phytochemicals of green banana flour (GBF). The influence of the drying temperature and thickness of the banana pulp slice were significant (p < 0.05) on the TPC and % inhibition of the DPPH radical. As the temperature increased from 60 to 80°C and the thickness decreased from 4 to 2 mm, the TPC values (225.69 ± 5.13 GAE/100 g DW) and % inhibition of the DPPH radical (91.08 ± 2.28%) were higher, respectively. Physicochemical properties such as: soluble solids, titratable acidity, pH and ashes were not influenced by DT and BST; and the humidity values were < 10%. These findings indicate that drying with hot air from 60 to 80°C and thicknesses <4 mm favor a greater conservation of the antioxidant capacity in banana flour.